Ibu Rumah Tangga Melawan Televisi: Studi Literasi Media Televisi Bagi Ibu Rumah Tangga di Tegalrejo Yogyakarta - Astuti, Yanti Dwi; Rifai, Akhmad; Ummatin, Khoiro (Sunan Kalijaga State Islamic University & The Asia Foundation, 2017)
The phenomenon of the television industry that is focused on rating, sharing, and advertising makes television programs more focused on entertainment programs rather than educational programs. The audience groups of television are mostly housewives who stay more at home and they are as a key figure in the education of children in the family. Strengthening the literacy media in Tegalrejo becomes important as the demographic condition shows that mostly the household mothers have low education levels, heterogeneous, and relatively poor. They spend more time watching television without attempting to criticize the content of the program. Moreover, the impressions and attitudes of the housewife are heavily influenced by the frequency of watching television. Therefore, we need to strengthen their literacy media to prevent the negative effect of television and to shape the audience to be more critical and smarter in watching the television. This research uses community-based research (CBR), which actively involves the community. The implementation of strategy in media literacy training begins with the activities of related studies to gain a better understanding about the media literacy, the position and role of housewives in observing and selecting media content through seminars and workshops, pre- and post-test about media literacy. Furthermore, learn the discourse from various groups of societies related to their views and opinions on media literacy movement. After a series of activities have been completed, it was found the testimonies from participants about the broadcasting picture in Indonesia and an image, message, and their expectations for the improvement of broadcasting in Indonesia.[Fenomena industri televisi yang fokus pada rating, share dan advertising membuat program televisi lebih fokus pada program hiburan dan mengesampingkan program edukasi. Kelompok pemirsa televisi dari kalangan ibu rumah tangga tinggal lebih lama di rumah dan mereka adalah tokoh sentral dalam pendidikan anak-anak dalam keluarga. Penguatan media literasi di Tegalrejo menjadi penting karena kondisi demografi di daerah tersebut berpendidikan rendah, heterogen dan relatif miskin. Mereka menghabiskan lebih banyak waktu di depan televisi, menonton televisi di rumah tanpa ada usaha untuk mengkritik konten tayangan acara televisi dan sikap yang tampak pada ibu rumah tangga sangat dipengaruhi oleh jumlah frekuensi mereka menonton tayangan televisi sehingga perlu penguatan literasi televisi guna melawan dampak negative televisi dan mewujudkan penonton yang cerdas, kritis dalam menonton acara televisi. Penelitian ini merupakan bentuk penelitian yang melibatkan peran serta komunitas (Community Base Research). Strategi implementasi pelatihan literasi media diawali dengan kegiatan studi terkait untuk memahami literasi media, posisi dan peran ibu rumah tangga dalam melihat dan memilih konten media melalui seminar dan workshop, pra dan post-test tentang literasi media. Selanjutnya, wacana dari berbagai kalangan masyarakat terkait pemikiran mereka terhadap gerakan literasi media. Setelah serangkaian kegiatan selesai, ditemukan kesaksian dari peserta tentang gambaran penyiaran di Indonesia dan sebuah citra, pesan dan harapan mereka untuk penyempurnaan penyiaran di Indonesia.]